Prior Opinion, Debt Default dan Ukuran Perusahaan Pengaruhnya Terhadap Penerimaan Opini Audit Going Concern - Eka Hariyani; Meilda Wiguna; Hardi (Jurnal Akuntansi Keuangan dan Bisnis, 2021)
Going concern is an important issue to deal with because it determines how the business will survive. One of the going concern indicators that will be evaluated by stakeholders is the going concern opinion issued by the auditor. The purpose of this study was to examine the effect of Prior Opinion, Debt Default and Company Size on Acceptance of Going Concern Audit Opinions. The sample consists of 80 manufacturing companies listed on the Indonesia Stock Exchange from 2013-2017. Data analysis using logistic regression analysis (logistic regression). The results showed that the prior opinion and company size had an influence on the company's decision makers in conducting going concern audit opinion. This indicates that the auditor considers the company's previous condition to evaluate current going concern problems, because going concern problems are difficult to solve in the short term. Meanwhile, Debt Default has no effect on going concern problems, this has implications for the company to maintain business continuity and auditors to consider the company's previous conditions to issue current audit opinions.